Contextual Problem Solving and Adaptive Logics In Creative Processes - Batens, Diderik (Philosophica, 1999)
Creativity is commonly seen as beyond the scope of rationality. In the present paper, it is argued that available insights in epistemology and available results in logic enable us to incorporate creativity within an independently sensible view on human rationality.